An improved chromogenic substrate endotoxin assay for clinical use. Issue 10 (October 1983) - Harris, R I; Stone, P C; Stuart, J
Abstract : An improved quantitative assay for endotoxin in plasma was developed after evaluating three different chromogenic substrates and seven methods for removal of plasma inhibitors. Optimal storage conditions for plasma samples prior to assay were also determined. Using chromogenic substrate S2423 with plasma diluted 1/10 in water and heated to 75 degrees C for 5 min to remove inhibitors, a within-batch coefficient of variation of 4% was obtained at levels of endotoxin likely to be encountered clinically. The limit of assay sensitivity was less than 10 pg/ml. This assay provides a sensitive quantitative test for single episodes of endotoxaemia in individual patients but variable activation of the Limulus proenzyme by endotoxin from different bacterial strains limits quantitative comparisons between patients.